2007
DOI: 10.21608/jvmr.2007.77896
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetic and renal clearance study of ceftiofur in cross breed Friesian and Buffalo calves

Abstract: The pharmacokinetic profile of ceftiofur sodium, a third generation cephalosporin, was studied in both Friesian and buffalo calves following a single intravenous and intramuscular administration of 2.2 mg kg -1 b.wt. in a cross over study with 15-day wash out period. After i.v administration the serum concentration-time curve of ceftiofur sodium was best fitted using two-compartments open model, with distribution half-lives (t ½(α) ) of 0.384 and 0.176 h., elimination half-lives (t ½(β) ) of 5.047 and 1.607 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Cefotaxime was transferred from central to peripheral compartment at a slower rate (K12 =1.51 h -1 ) than its passage from peripheral compartment to central compartment (K21 = 1.02 h -1 ). These values were nearly similar to that reported for ceftiofur in buffalo calves (K12 = 1.557 h -1 ) and (K21 = 2.003 h -1 ) by El-Gendy et al, (2007) and cefquinome in chickens (K12 = 0.713 h -1 ) and (K21 = 1.06 h -1 ) by El-Sayed et al, 2015c).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Cefotaxime was transferred from central to peripheral compartment at a slower rate (K12 =1.51 h -1 ) than its passage from peripheral compartment to central compartment (K21 = 1.02 h -1 ). These values were nearly similar to that reported for ceftiofur in buffalo calves (K12 = 1.557 h -1 ) and (K21 = 2.003 h -1 ) by El-Gendy et al, (2007) and cefquinome in chickens (K12 = 0.713 h -1 ) and (K21 = 1.06 h -1 ) by El-Sayed et al, 2015c).…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, this Vdss value was higher than those recorded for ceftriaxone in dogs (0.217 L/kg; Rebuelto et al, 2002); cefepime in calves and ewes (0.21 and 0.32 L/kg; Ismail, 2005a;Ismail, 2005c, respectively;ceftiofur in calves (0.134 L/kg;El-Gendy et al, 2007); ceftiofur in camel (0.13 L/kg; Goudah, 2007); ceftiofur in cow (0.178 L/kg; Tohamy, 2008); ceftriaxone in buffalo (0.36 L/kg;Gohil et al, 2009 ); cefpirome in cow calves (0.33 L/kg; Patel et al, 2013);ceftiofur in chickens (198.60 On the other hand, volume of distribution (Vdss) was shorter than that recorded in cefepime in rabbits (1.168 L/kg; Abd El-Aty et al, 2007); ceftriaxone in domestic cats (0.57 L/kg; Albarellos et al, 2007); cefepime in sheep (0.42 L/kg; Patel et al, 2010); cefoperazone in sheep (0.51 L/kg; Soni et al, 2012) and cefquinome in goats (0.51 L/kg; Dumka et al, 2013).…”
Section: Discussionmentioning
confidence: 57%
“…IV injection was equal to 5.700 h. This observation agreed with the data reported after IV administration of ceftiofur in cows and calves (t 0.5(β) ) =5.09, 5.05 h by(El- Gendy 2007 andTohamy, 2008), respectively.…”
supporting
confidence: 89%
“…Using this experimental design we found no significant difference between D 50 for the silt-loam and sandy soil types ( P = 0.93), and there was an expected dose response with D 50 being greater for 100 ppm compared to 50 ppm ( P = 0.044). Subsequent analyses used sandy soil and 50 ppm CFM in urine as a standard concentration (CFM concentrations in urine range from ∼7 to 165 ppm within 24 h of ceftiofur administration [21] ). The D 50 value of filter-sterilized urine alone with 50 ppm CFM was >110 days at both 23°C and 4°C indicating that abiotic hydrolysis of CFM was negligible during the course of these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Urine used in these experiments was collected from a single month-old male calf and was collected aseptically in sterile bottles both before and after administration of a single dose of ceftiofur sodium (Naxcel, 2.2 mg/kg body weight, intramuscular). El Gendy et al reported that after intramuscular administration of ceftiofur calves excreted most of the ceftiofur metabolites in the first 4 h post-injection and thus we collected urine up to 8 h post-injection [21] . The collected urine was filter-sterilized (0.22 µm pore size) and stored at –20°C until further use.…”
Section: Methodsmentioning
confidence: 99%